Evolução do comportamento social: dinâmica evolutiva dos animais eussociais - Daniel de Assis Rodrigues (2020)
Natural selection is the process by which characteristics best adapted to the environment that are hereditary become more common in a population due to the greater probability of survival and reproduction of individuals with the best adapted characteristic. Therefore, when a certain characteristic is observed in a population, it is assumed that one of the effects of that characteristic is the increase, for example, in the reproduction rate of individuals with this characteristic. However, a particular set of animal species, called eusocial, exhibit the presence of sterile castes. In other words, natural selection favored the appearance of animals, such as ants, for example, in which a large number of individuals have no reproductive potential. Therefore, the conditions for the evolution of eussocial species are somewhat intriguing. Currently, two aspects of mathematical formalization of the evolution of eussociality stand out: standard natural selection, which is based on the notion of direct reproductive fitness, and kin selection, which is based on the notion of inclusive fitness. In this sense, the present work had as its first goal to describe the concepts of social fitness as well as Hamilton’s rule and to analyze its limitations through the evolutionary game theory. The analysis employed showed that there are limitation for the validity of inclusive fitness theory such as: low selection and low mutation limits, additivity and condition population with a special structure, while the usual approach to standard natural selection remains promising since none of the previous requirements are present. So, this comparison serves as a basis to analyze the main hypotheses for the evolution of eussociality: the haplodiploidy hypothesis, the ancestral monogamy hypothesis, ecological hypothesis and the group selection hypothesis. The latter being the most promising, not only because it avoids the limitations of social fitness concepts, but also because is yields a simple analysis of structured population subject to natural selection. In addition, the phenomenon of the transition from primitive social behaviors to eussociality through the Parasocial and Subssocial evolutionary routes was explored through two constructive mathematical operations: coming-together (C-T) and stay-together (S-T). The study of these two construction operations enabled the principle of an approach, through computer simulations, to explore which of the two routes was the most likely, and under what conditions they are possible, for some of the main groups of eussocial animals.